2021
DOI: 10.1002/jctb.6984
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom tyrosinase immobilized in metal–organic frameworks as an excellent catalyst for both catecholic product synthesis and phenolic wastewater treatment

Abstract: BACKGROUND Metal–organic frameworks (MOFs) have gained increasing attention with ever‐expanding applications. Developing new MOF‐based immobilized enzymes with new applications is required, not only for demonstrating the generality and applicability of using MOFs for enzyme immobilization, but also to provide potential biocatalysts for industrial applications. To the best of the authors’ knowledge, this is the first report of immobilizing mushroom tyrosinase on zeolitic imidazolate frameworks (ZIFs), with two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In the FTIR spectra of tyrosinase CLEAs and mCLEAs, the enzymes’ characteristic absorption bands known as Amide I (peaks at 1654 and 1652 cm −1 ), Amide II (1540 cm −1 ) and Amide III (peaks in the range of 1250–1350 cm −1 ) are observed for both biocatalytic systems. These bands are mostly associated with the C=O stretching vibration (Amide I), the N-H bending vibration and the C-N stretching vibration (Amide II and Amide III) [ 26 ]. FTIR analysis has also been used by other researchers with the aim of proving the successful preparation of cellulase CLEAs and cellulase magnetic CLEAs, by observing similar bands [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the FTIR spectra of tyrosinase CLEAs and mCLEAs, the enzymes’ characteristic absorption bands known as Amide I (peaks at 1654 and 1652 cm −1 ), Amide II (1540 cm −1 ) and Amide III (peaks in the range of 1250–1350 cm −1 ) are observed for both biocatalytic systems. These bands are mostly associated with the C=O stretching vibration (Amide I), the N-H bending vibration and the C-N stretching vibration (Amide II and Amide III) [ 26 ]. FTIR analysis has also been used by other researchers with the aim of proving the successful preparation of cellulase CLEAs and cellulase magnetic CLEAs, by observing similar bands [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosinase has been immobilized on various carriers and its biocatalytic properties have been studied and compared to those of the free enzyme [ 25 , 26 , 27 , 28 , 29 ]; these studies showed that the immobilized form exhibits enhanced activity and stability. Cross-linking of enzyme molecules is another immobilization technique used for tyrosinase.…”
Section: Introductionmentioning
confidence: 99%
“…Especially for Lac, this technology showed great application potential in the field of pollutant degradation. Wei et al reported for the first time the complete removal of eliminated phenol, p-cresol, and p-chlorophenol by immobilizing tyrosinase on Zeolite imidazole framework-8 (ZIF), which showed high efficiency in the degradation of phenolic pollutants [29]. Jiang et al prepared Lac at Cu (PABA) using an efficient one-pot approach.…”
Section: The De Novo Methodsmentioning
confidence: 99%
“…This feature effectively shields enzymes from external environmental influences to some extent, thereby enhancing their stability. MOF−enzyme composites, particularly those involving ZIF-8, have found widespread application in the degradation of industrial dyes, 53 phenolic compounds, 54 and pesticides. 55 Regrettably, the ZIF-8 shell presents a limitation with its narrow aperture (3.4 Å), significantly impeding the diffusion of organic pollutants and consequently slowing down pollutant degradation.…”
Section: Surface Immobilizationmentioning
confidence: 99%